Analisa Kelayakan Penggunaan Pembangkit Listrik Tenaga Surya Pada Bank Nagari Cabang Lubuk Gadang Menggunakan Metode Kelayakan Investasi - Setiawan, Harry; Bandri, Sepannur; Dewi, Arfita Yuana (LPPM Politeknik Jambi, 2025)
The potential for solar energy is immense, as the sun is an abundant source of renewable energy worldwide, especially in Indonesia. Indonesia receives sunlight for 10 to 12 hours per day. Numerous studies on the use of solar power plants have shown promising payback period results less than 10 years which is relatively fast compared to the economic lifespan of solar panels, which can last up to 25 years. PT Bank Nagari, a bank owned by the Provincial Government of West Sumatra and various regional governments within West Sumatra, consistently promotes a culture of efficiency to enhance revenue and support the company’s growth and regional development. Considering the fast capital return on solar power investments and the alignment with Bank Nagari's culture of efficiency and revenue optimization, a feasibility study was deemed necessary. This study aimed to analyze the feasibility of using a solar power plant at Bank Nagari Lubuk Gadang Branch using investment feasibility methods to determine whether the project could enhance the company's efficiency and revenue. However, the research concluded that the investment in the solar power plant was not feasible, as the returns were lower compared to the current business activities run by PT Bank Nagari Lubuk Gadang Branch.